2017
DOI: 10.1080/21663831.2016.1276485
|View full text |Cite
|
Sign up to set email alerts
|

Silver-rich clusters in nanoporous gold

Abstract: High-resolution elemental mapping in a transmission electron microscope shows that the residual silver in dealloying-made nanoporous gold (NPG) is aggregated in nanoscale clusters. Kinetic Monte Carlo simulation confirms that these regions are buried relics of the master alloy that have never been exposed to corrosion. The surface of as-dealloyed NPG is covered by at least one atomic monolayer of nearly pure gold. The preferential location of silver in the bulk is relevant when interfaces control the material'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 43 publications
4
85
1
Order By: Relevance
“…For the "percolation dissolution" scenario, in which bulk nanoporosity can be formed, Figure 3 illustrates the important steps of the microstructure evolution during percolation dissolution. 19 Intense interest in dealloying as a route to the manufacture of porous nanomaterials evolved only after it was shown that the dealloying pattern formation process could be understood in terms of modern concepts of driven processes in alloys far from equilibrium. 16 That same study also suggested the use of nanoporous metals for sensing applications.…”
Section: Dealloying-from Corrosion Science To the Physics Of Dealloyimentioning
confidence: 99%
“…For the "percolation dissolution" scenario, in which bulk nanoporosity can be formed, Figure 3 illustrates the important steps of the microstructure evolution during percolation dissolution. 19 Intense interest in dealloying as a route to the manufacture of porous nanomaterials evolved only after it was shown that the dealloying pattern formation process could be understood in terms of modern concepts of driven processes in alloys far from equilibrium. 16 That same study also suggested the use of nanoporous metals for sensing applications.…”
Section: Dealloying-from Corrosion Science To the Physics Of Dealloyimentioning
confidence: 99%
“…EDS measurements might underestimate the actual Co‐concentration in the clusters, as they are buried under Pd‐rich surface layers, which dominates the EDS signal. Clustering of the residual element is a direct result of surface diffusion during the dealloying process, which has been studied in nanoporous Au(Ag) recently …”
Section: Resultsmentioning
confidence: 99%
“…Regarding magnetic applications, a proper adjustment of both size and distance between the Co‐rich clusters in npPd(Co), which can be adjusted via dealloying parameters or by thermal treatment, might allow a tuning of the magnetic response for specific problems. We believe that the magneto‐ionic switching of superparamagnetism offers great application potential for microelectromagnets or spintronics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…preparation of lamellae), which carries the risk of structural damage. In this context, non‐invasive three‐dimensional (3D) imaging methods based on computed tomography are beginning to receive significant attention for characterisation of heterogeneous catalysts, including nanoporous gold . By revealing both exterior and interior structural features, tomographic analysis can derive surface area, porosity and pore size distribution data from the sample together with pore network mapping in 3D, as demonstrated recently for nanoporous silver .…”
Section: Introductionmentioning
confidence: 99%